Evolução molecular, análise multilocus e diferenciação entre espécies do grupo fraterculus (Diptera, Tephritidae) - Lima, André Luís Andrade (Universidade Federal de São Carlos, 2011)
The Tephritidae includes approximately 4500 species described to date and many of these species make up the main genera of economic importance: Anastrepha, Bactrocera and Ceratitis. The genus Anastrepha is among the Tephritidae with greatest diversity in the Americas including 230 described species, among which some species with great economic importance because they represent important fruit pests. There is evidence that species in the fraterculus group have diverged recently, even having some cryptic species. Because of this, species in the fraterculus group are a great system for evolutionary studies. For evolutionary studies, it is necessary to evaluate the rates of molecular evolution and their role in identifying rates of gene flow and population differentiation, the construction of tree species and a possible separation for the species. Seeking a better understanding of the fraterculus group, we chose three species of this group, Anastrepha obliqua, A. fraterculus and A. sororcula as models for this study and five genes isolated from a cDNA library of reproductive tissues of Anastrepha. Several genes that are expressed in reproductive tissues have a higher divergence rate THAN those expressed in non-reproductive tissues, may thus give evidence of reproductive isolation. In this work, we found evidence of positive diversifying and positive selection for a couple of genes (CG11912 and CG10031), and high levels of polymorphism, although they failed to meet statistical significance for positive selection, in other genes here studied, such as ,Lcp65Ac and CG16712, whereas Df31 was more conserved. An analysis of molecular variance found that levels of genetic polymorphism are best explained by differences between species THAN between geographic regions. Haplotype networks for each gene failed to differentiate the species here studied and showed high levels of shared polymorphism among the species, with some rare exceptions. On the other hand, a joint analysis of these data to try to infer a species tree indicate a strong cohesion for populations of A. obliqua from the Brazilian Northeast and Southeast while for A. fraterculus and A. sororcula we observed a substructure that separated Southeeast populations of A. sororcula, which was well defined, from Northeast populations, which may be hybridizing with populations of A. fraterculus from the Northeast, due to great number of shared polymorphisms. Other THAN populations in the Brazilian northeast, A. fraterculus also forms a separate, though short, lineage. Considering these findings, a broader sampling is needed, especially in areas not yet collected particularly in the Northeast, seeking to untangle the phylogenetic relationships not only among these species, but also other species of the fraterculus group.
Keywords: Genética e evolução; Tephritidae; Anastrepha; Evolução molecular; Análise multilocus; Tephritidae; Anastrepha; Molecular evolution; Multilocus analysis; CIENCIAS BIOLOGICAS::GENETICA